Proceedings of SPE Improved Oil Recovery Symposium 2010
DOI: 10.2523/129923-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Process for Manufacturing and Stabilizing High-Performance EOR Surfactants at Low Cost for High-Temperature, High-Salinity Oil Reservoirs

Abstract: An alcohol dimerization process known as the Guerbet reaction is used to create large alcohol structures for the production of the corresponding alkoxy sulfate surfactants. In the alcohol industry, Guerbet (dimer) alcohols are considered the "gold" standard for large, branched alcohols. These Guerbet alcohols tend to be more expensive than other alcohols when produced in high purity for various industrial applications. The high cost is mainly due to driving the reaction to completion and/or stripping-off of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…For example, Zhao et al (2008) showed that internal olefin sulfonate (IOS) surfactants with high carbon numbers such as C 20-24 IOS and C 24-28 IOS were more effective at reducing IFT than surfactants with shorter hydrophobes. As described by Adkins et al (2010), Guerbet alkoxy sulfates (GAS) is another class of surfactants that can be made with even larger hydrophobes at lower costs. GAS surfactants show exaggerated hydrophobicity, because of its near mid-point branched alcohols with long twin tails.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhao et al (2008) showed that internal olefin sulfonate (IOS) surfactants with high carbon numbers such as C 20-24 IOS and C 24-28 IOS were more effective at reducing IFT than surfactants with shorter hydrophobes. As described by Adkins et al (2010), Guerbet alkoxy sulfates (GAS) is another class of surfactants that can be made with even larger hydrophobes at lower costs. GAS surfactants show exaggerated hydrophobicity, because of its near mid-point branched alcohols with long twin tails.…”
Section: Resultsmentioning
confidence: 99%
“…As sulfonates in general are more expensive than sulfates, the costs were prohibitively high in some cases for EOR to be even considered. However, recent advancements in stabilizing sulfates at high temperatures (Adkins et al, 2010) have enabled ES to be considered for high temperature EOR applications, thus expanding the selection of surfactants immensely. Laboratory testing of these ES surfactants under optimum conditions has shown them to be effective at high temperature and they can be made at low cost.…”
Section: Application To Harsh Reservoir Conditionsmentioning
confidence: 99%
“…The surfactant formulation consisting of 0.15% TDA-13 PO SO 4 -, 0.15% C19-23 IOS with 1% IBA-5EO co-solvent showed ultra-low IFT, suitable aqueous stability and low microemulsion viscosity. Alkyl alkoxy sulfates have been shown to have a long half life even at 100°C in the presence of sodium carbonate (Adkins et al, 2010). Figure 11 details the activity map for the ASP-2.1 flood, and the salinity gradient used.…”
Section: Crude Oil #1 Corefloods: Proof Of Acp Concept In Outcrop Andmentioning
confidence: 99%
“…The design of an ASP formulation for this reservoir has previously been presented (Levitt et al, 2012). However due to the high temperature and probable presence of anhydrite, it was decided that the use of sulfate surfactants, which require high pH and thus the successful propagation of alkali for stability at elevated temperatures (Adkins et al, 2010), presents an unnecessary risk in this case. A new formulation was thus optimized without alkali, using proprietary, high-salinity tolerant, anionic surfactants (patent pending).…”
Section: Surfactant Phase Behavior Formulationmentioning
confidence: 99%